Sunscreen Test of Methanol Extract, N-Hexane, Ethyl Acetate and Methanol-Water Fraction of Artocarpus lanceifolius Roxb. Leaves Based on In Vitro Method - Eva Marliana; Novia Rahmawati Isyahro; Nanang Tri Widodo (Jurnal Ilmiah Sains, 2023)
Sunscreen test of  keledang (Artocarpus lanceifolius Roxb.) leaves based on in vitro method was carried out. This research aimed to investigate the property of sunscreen from methanol extract, n-hexane, ethyl acetate and methanol-water fraction of keledang leaves. The methods used include the in vitro methods by using spectrophotometer UV-Vis. Based on results of phytochemical test, it was known that  methanol extract contains flavonoids, phenolics, steroids/triterpenoids. n-Hexane fraction contains steroids/triterpenoids and quinones. Ethyl acetate fraction contains flavonoids, phenolics, steroids/triterpenoids and quinones. Methanol-water fraction contains flavonoids and phenolics. Methanol extract, n-hexane, ethyl acetate and methanol-water fraction also showed sunscreen activity based on the SPF value at a concentration of 25; 50; 100; 150; 200 and 250 mg/L. Crude methanol extract has SPF value respectively were 4.44; 7.36; 15.15; 22.47; 31.25 and 37.31 (minimum-ultra). N-Hexane fraction has SPF value respectively were 1.37; 2.24; 5.07; 7.51; 10.01 and 12.74 (minimum-maximum). Ethyl acetate fraction has SPF value respectively were 3.321; 7.20; 13.03; 19.54; 25.97 and 30.59 (minimum-ultra). Methanol-water fraction has SPF value respectively were 5.24; 10.87; 21.48; 30.89; 36.01 and 38.52 (medium-ultra). The SPF value increases with increasing concentration because the higher the concentration, the more active sunscreen compounds contained in the extract and fraction. In keledang leaves, methanol-water fraction has the highest suncreen activity folowed by methanol extract, ethyl acetate fraction and n-hexane fraction. Keledang leaves have a potency as  sunscreen agent. Keywords: Artocarpus lanceifolius; in vitro; sunscreen